Signal Processing Approaches to Secure Physical Layer Communications in Multi-Antenna Wireless Systems - Hong, Y.-W. Peter; Lan, Pang-Chang.; Kuo, C.-C. Jay.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
This book introduces various signal processing approaches to enhance physical layer secrecy in multi-antenna wireless systems. Wireless physical layer secrecy has attracted much attention in recent years due to the broadcast nature of the wireless medium and its inherent vulnerability to eavesdropping. While most articles on physical layer secrecy focus on the information-theoretic aspect, we focus specifically on the signal processing aspects, including beamforming and precoding techniques for data transmission and discriminatory training schemes for channel estimation. The discussions will cover cases with collocated and with distributed antennas, i.e., relays. The topics covered will be of interest to researchers in the signal processing community as well to practitioners and engineers working in this area. This book will also review recent works that apply these signal processing approaches to more advanced wireless systems, such as OFDM systems, multicell systems, cognitive radio, multihop networks etc. This will draw interest from researchers that wish to pursue the topic further in these new directions. This book is divided into three parts: (i) data transmission, (ii) channel estimation and (iii) advanced applications. Even though many works exist in the literature on these topics, the approaches and perspectives taken were largely diverse. This book provides a more organized and systematic view of these designs and to lay a solid foundation for future work in these areas. Moreover, by presenting the work from a signal processing perspective, this book will also trigger more research interest from the signal processing community and further advance the field of physical layer secrecy along the described directions. This book allows readers to gain basic understanding of works on physical layer secrecy, knowledge of how signal processing techniques can be applied to this area, and the application of these techniques in advanced wireless applications.
Background on Information-Theoretic Security -- Secrecy Precoding and Beamforming Multi-Antenna Wireless Systems -- Secrecy in Relay and Distributed Antenna Systems -- Secrecy from the Channel Estimation Perspective -- Secrecy in Advanced Wireless Applications.
Keywords: Engineering; Data protection; Telecommunication; Engineering; Signal, Image and Speech Processing; Systems and Data Security; Communications Engineering, Networks